Total Daily Energy Expenditure is Overestimated by Dietary References Intake Equations Compared with Doubly Labeled Water in A Sample of Brazilian Adolescents - Bérgamo Silva Lara; Antonio dos Anjos Luiz; Gallo Rosenburg Meire; Maira da Cruz Alves Natália; de Fátima Micheletto Rutinéia; Ferriolli Eduardo; Pfrimer Karina (International Journal of Nutrition, 2024)
Objective This report aimed to compare the total daily energy expenditure (TDEE) of adolescents measured by doubly labeled water (DLW) with the 2005 and 2023 dietary reference intake (DRI) equations proposed by the Institute of Medicine (IOM) in a sample of Brazilian adolescents. Methodology: This is a cross-sectional and observational study with a convenience sample of 15 obese and eutrophic adolescents, aged between 11 and 14 years, from public schools and the obesity outpatient clinic of the Clinics Hospital of the Ribeirão Preto Medical School – University of São Paulo (HC FMRP-USP) in Brazil. Were obtained stature and weight by conventional methods and used to calculate the body mass index (BMI) to determine the nutritional status. Fat-free mass (FFM) was measured using dual-energy X-ray absorptiometry. Energy expenditure was determined by DLW and estimated by the 2005 and 2023 DRI equations. The level of physical activity was measured with the ActivPAL™ accelerometer to classify adolescents within the equations. Results: Forty-seven percent of the sample were eutrophic and 53% were obese. The adolescents were classified as somewhat active according to the average number of daily steps. The DLW-derived TDEE and the TDEE derived from the 2005 and the 2023 predictive equations are presented as means, standard deviations, and 95% confidence intervals (CI). The 2005 and 2023 DRI equations produced significantly higher values than the DLW-determined TDEE (56.2% and 57.2%, respectively). Conclusion: Additional studies with Brazilian adolescents should be conducted to propose more accurate and specific predictive TDEE equations.
Keywords: Energy expenditure